2001
DOI: 10.1029/2000jd900667
|View full text |Cite
|
Sign up to set email alerts
|

Deviation from reciprocity in bidirectional reflectance

Abstract: Abstract. The subject of the paper is to discuss and quantify deviations from reciprocity of the bidirectional reflectance distribution function (BRDF), i.e., the difference of BRDF obtained when inverting illumination and viewing directions. Directional reciprocity is not valid in general, because when the illumination beam has a spatial extension larger than the viewed area (as is most often the case for BRDF measurements), some of the scatterers building up the observed radiance are located at different pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…It is indeed consistent with realworld satellite observations of reciprocity violation uncovered by DiGirolamo et al [61] in spatially variable cloud scenes inside a relatively broad field of view, and readily replicated with numerical Monte Carlo simulations. These findings were soon explained theoretically by Leroy [62]. This provides an element of validation of the new model and, by the same token, invalidates for atmospheric applications all models for RT in stochastic media based on either homogenization or linear mixing.…”
Section: Single Scattering In D = 3: Violation Of Angular Reciprocitymentioning
confidence: 96%
“…It is indeed consistent with realworld satellite observations of reciprocity violation uncovered by DiGirolamo et al [61] in spatially variable cloud scenes inside a relatively broad field of view, and readily replicated with numerical Monte Carlo simulations. These findings were soon explained theoretically by Leroy [62]. This provides an element of validation of the new model and, by the same token, invalidates for atmospheric applications all models for RT in stochastic media based on either homogenization or linear mixing.…”
Section: Single Scattering In D = 3: Violation Of Angular Reciprocitymentioning
confidence: 96%
“…While Helmoltz reciprocity approximately holds in our dataset, we found that large discrepancies occur when assuming bilateral symmetry during polarized measurements. Similar observations were made in prior studies of polarized reflectance [Clarke and Parry 1985;Leroy 2001] and diffuse-specular pBRDFs [Baek et al 2018]. For this reason, our pBRDF parameterization uses ∈ [− , ] in contrast to previous BRDF datasets.…”
Section: Polarimetric Brdfmentioning
confidence: 77%
“…Note that both Minnaert and Lommel-Seeliger functions are also reciprocal. However, several studies question the reciprocity of the surface BRDF (Kriebel 1996, Li et al 1999, Leroy 2001, Snyder 2002.…”
mentioning
confidence: 99%